Pengaruh Jarak Elektroda Dan Kuat Arus Pada Pengolahan Air Gambut Dengan Proses Elektrokoagulasi Secara Kontinu - Albi Fadhlah Ramadhan; Idral Amri; Drastinawati Drastinawati (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2021)
Peat water is surface water that inundates an area, formed from a pile of organic material for a long time. Peat water can cause skin irritation and metabolic disorders. The purpose of this study was to determine the application of the electrocoagulation method can be used to neutralize pH, and reduce levels of TSS and Fe in peat water treatment and also to determine the effect of changes in electrode spacing and current strength on decreasing TSS and Fe levels and neutralizing the pH of peat water. The parameters tested include pH, TSS (Total Suspended Solid), and Fe. The electrocoagulation process uses electric power which flows in the direction through the electrodes. Electrocoagulation reactor paired with a cable connected to the power supply and then connected to an electric current with a variation of current strength (1.0; 1.4; and 1.8 A) and electrode distance variations (0.5; 0.75; 1 inch). The results of this study giving the optimum conditions obtained at a strong current of 1.8 A and 0,75 inch electrode distance with an increase in pH from 3.5 to 6.8, a decrease in TSS from 128 to 36 mg / L, a decrease in Fe of 78.9% from 2.405 mg / L to 0.506 mg / L.